Percutaneous endoscopic transforaminal discectomy precedes interlaminar discectomy in the efficacy and safety for lumbar disc herniation. Issue 2 (15th February 2019) - Chen, Peng; Hu, Yihe; Li, Zhanzhan
Abstract : We searched several databases from the times of their inception to 20 December 2018. Randomized controlled trials and cohort studies that compared percutaneous endoscopic transforaminal discectomy (PETD) with percutaneous endoscopic interlaminar discectomy (PEID) were identified. We used a random-effects model to calculate the relative risks (RRs) of, and standardized mean differences (SMDs) between the two techniques, with 95% confidence intervals (CIs). Twenty-six studies with 3294 patients were included in the final analysis. Compared with PEID, PETD reduced the short-term (SMD −0.68; 95% CI −1.01, −0.34; P =0.000) and long-term (SMD −0.47; 95% CI −0.82, −0.12; P =0.000) visual analog scale scores, blood loss (SMD −4.75; 95% CI −5.80, −3.71; P =0.000), duration of hospital stay (SMD −1.86; 95% CI −2.36, −1.37; P =0.000), and length of incision (SMD −3.93; 95% CI −5.23, −2.62; P =0.000). However, PEID was associated with a lower recurrence rate ( P =0.035) and a shorter operative time ( P =0.014). PETD and PEID afforded comparable excellent- and good-quality data, long- and short-term Oswestry disability index (ODI) scores, and complication rates. PETD treated lumbar disc herniation (LDH) more effectively than PEID. Although PETD required a longer operative time, PETD was as safe as PEID, and was associated with less blood loss, a shorter hospital stay, and a shorter incision. PETD is the best option for patients with LDH.